Micro-biological degradation and transformation of dissolved organic matter following continuous cropping of tobacco - Chen, Peng; Wang, Lei; Li, Wei-hua; Zhang, Xiu-xia; Gao, Huan-huan; Zhou, Xian-hong; Zhuang, Qian-ying; Li, Jian; Li, Xing-yue; Zhang, An-sheng (Frontiers in Microbiology, 2024)
In recent years, the problems associated with continuous cropping (CC) that cause soil degradation have become increasingly serious. As a key soil quality property, dissolved organic matter (DOM) affects the circulation of carbon and nutrients and the composition of bacterial communities in soil.However, research on the changes in the molecular composition of DOM after CC is limited. In this study, the soil chemical properties, DOM chemical diversity, bacterial community structure, and their interactions are explored in the soil samples from different CC years (CC1Y, CC3Y, CC5Y, and CC7Y) of tobacco. With increasing CC year of tobacco, most of the soil chemical properties, such as total carbon, total nitrogen and organic matter, decreased significantly, while dissolved organic carbon first decreased and then increased. Likewise, the trends of DOM composition differed with changing duration of CC, such as the tannin compounds decreased from 18.13% to 13.95%, aliphatic/proteins increased from 2.73% to 8.85%. After 7 years of CC, the soil preferentially produced compounds with either high H/C ratios (H/C > 1.5), including carbohydrates, lipids, and aliphatic/proteins, or low O/C ratios (O/C < 0.1), such as unsaturated hydrocarbons. Furthermore, core microorganisms, including Nocardioides, wb1-P19, Aquabacterium, Methylobacter, and Thiobacillus, were identified. Network analysis further indicated that in response to CC, Methylobacter and Thiobacillus were correlated with the microbial degradation and of DOM. These findings will improve our understanding of the interactions between microbial community and DOM in continuous cropping soil.